PEMBERDAYAAN NELAYAN DALAM MENINGKATKAN KESEJAHTERAAN KELUARGA DI DESA TULEHU KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Ingriyani Banyal; Nurul Amalia; Umi Kalsum Hehanussa (CV. ADIBA AISHA AMIRA, 2024)
The lives of fishing communities in Indonesia who live in coastal areas are synonymous with low welfare (poverty) and backwardness. In this case, the fishing community has its own social characteristics which are very different from other community groups, especially the fishing community on the coast of Tulehu State, Central Maluku Regency, where the majority of the population makes their living as fishermen. This research aims to find out 1). How is Empowerment carried out by the Tuna Abadi fishermen group in Tulehu Country 2). What is the level of welfare of Tuna Abadi fishing families in Tulehu Country. This type of research is descriptive qualitative with data collection techniques through observation, interviews, documentation. Qualitative data analysis techniques include data reduction, data presentation and drawing conclusions. The results of this research show that 1). Efforts made by the